The social meanings of coffee consumption in Brunei: A sociological exploration - Rizal, Waliyah Haji Mohammad Saiful; Alam, Meredian (Center for Sociological Studies and Community Developmen, 2025)
Coffee, as one of the world’s principal commodities, has long been connected with Western culture in the beverage industry. This study explores the reasons of the stated phenomenon, why it arose, the social significance and meanings of consuming coffee, and lastly, the influences of coffee culture on individuals' lifestyles through coffee consumption in Brunei. This study employed a qualitative technique, including interviews via an online conferencing platform Zoom, which involved 11 respondents aged 17-47 years-old occupying various professions such a manager, clerks, teachers, and officers as well as graduate students. This original article discovered that consumers consumed coffee leading to particular social meanings, including prestige and productivity, symbolism, personal recollections and nostalgia, and social features attributed to coffee consuming activities. Coffee was also consumed as a lifestyle habit and daily routine, as well as connoisseurship from establishing an acquired taste and social identity constructs. It is worth-noting that the shift in social meaning about coffee consumption in Brunei is dynamic, complexed, and obviously inseparable from one another. Our interview accounts also unfold that there is a sensuous juxtaposition within these socio-cultural elements of coffee emanating from subjective experiences of regularly consuming specific coffee brands in selected cafes, which also embody pivotal ambiences.